Influence of organo-chemical fertilizer mixed with hormones on yield of Zea mays (L.) and soil productivity - Agbesi Kwadzo KETEKU; Pumisak INTANON (Acta Agriculturae Slovenica)
The effect of five fertilizers; NPK (15-15-15), organo-chemical hormone mixed formula 1 (HO-1), Formula 2 (HO-2), Formula 3 (HO-3) and granular organic fertilizer (GOF) were investigated on maize yield and soil properties in a Randomized Complete Block Design with 4 replications. The new hybrid maize (GT 822) was sown at 75 x 25 cm² spacing. The fertilizer rate was 300 kg ha-1. Initial soil analysis showed that the soil had a lower rate of nutrients but after the second season of trial a significant (p ≤ 0.05) improvement was observed in soil properties, the highest residual NPK of 0.875 %, 0.0275 %, and 0.0267 % were recorded in HO-3 plots. Vegetative data showed that maize height, dry matter, leaf area, and leaf chlorophyll of 270.85 cm, 282.66 g, 156.02 dm², and 56.70, respectively were also highest in HO-3 fertilizer. Plant growth indices; RGR, LAI, and dry matter use efficiency of 0.132 g g-1day-1, 5.90 and 34.4 %, respectively were best in HO-3. Grain yield and crude protein of 8276.68 kg ha-1 and 8.99 % were recorded in HO-3, followed by HO-2 and NPK. Lower yields were obtained from the control and GOF. Our finding revealed that the integration of nutrient sources in a balanced ratio produced the greatest yield output, improved soil properties, and is therefore the future approach to planning an effective fertilizer strategy. Reliance on GOF as a sole fertility package for maize production may result in significant yield losses compared to the integrated approach or use of NPK fertilizer.